Impact of large-scale social restrictions on air quality (NO₂, CO, O₃) during COVID-19: Surabaya case study, Indonesia - Asmaul Nur Fitria; Supriyadi Supriyadi; Muhammad Al-Irsyad; Anindya Hapsari (CV Rezki Media, 2025)
Background: The COVID-19 pandemic galvanized the world at the end of 2019. It was identified as an attack on humans and spread very quickly almost all over the world. As the person in charge of protecting the community, the government makes a policy that can suppress the spread of the COVID-19 virus. Objectives: This study aims to determine whether implementing large-scale social restrictions (PSBB) in the COVID-19 period (2020 to 2021) impacts air quality in Surabaya City, East Java. Methods: This quantitative research uses an Analysis of Secondary Data (ADS) approach by utilizing secondary data as the primary source. This research was conducted at the Surabaya City Environmental Service, East Java Province, in July - August 2021, with the total population being all the results of NO2, O3, and CO air quality measurements in 2020-2021 during the COVID-19 pandemic in January 2020 to December 2021 at monitoring stations in Surabaya City. This study uses Wilcoxon test analysis. Results: The results showed that implementing the first phase of large-scale social restrictions had no significant impact on NO₂ air quality in Surabaya City (p = 0.068). Implementing the transitional PSBB (second stage) had no significant impact on NO₂ air quality in Surabaya City (p = 0.068). Implementing the first and second phases of the PSBB has no significant impact on NO₂ air quality in Surabaya City (p = 0.173). Conclusions: The implementation of PSBB Phase One and PSBB Phase Two (transition period) did not significantly impact the air quality of NO2, CO, or O3 gases in Surabaya City. This finding challenges the common assumption that lockdowns automatically improve air quality and emphasizes the need for more comprehensive environmental policies.